Caracterização lectínica e avaliação do potencial antimicrobiano de frações proteicas das folhas de Combretum Leprosum Mart. - Duarte, Jady Alves (Universidade Federal Rural do Semi-Árido, 2021)
Bacterial resistance to antibiotics is one of the most visible examples of contemporary biological evolution, a result of the selective pressures promoted by the diversity and concentration of antibiotics used. The rampant use of antibiotics has led to the generation of a series of bacterial strains resistant to the strongest examples of antibiotics, and this has already become a major concern for the medical society. For agriculture, the presence in crops of phytopathogenic fungi resistant to fungicides is related to great economic losses with the destruction of plantations. Thus, the detection and bioprospecting of new molecules with antimicrobial action has become a current and necessary research area for the development of new control strategies for pathogenic microorganisms resistant to antibiotics already on the market. Combretum leprosum Mart. (Combretaceae), also known as mufumbo or beef, is a plant species of great ethnopharmacological importance; its tissues are used in folk medicine to treat various ailments. In addition to the biological effects of well-characterized secondary plant metabolites, the presence of bioactive lectins in C. leprosum leaves has been previously described. Due to their reversible and specific carbohydrate binding properties, these proteins promote varied biological actions on cells. The aim of this study was to characterize the lectin activity and investigate the antimicrobial potential of protein fractions obtained from C. leprosum leaves. The leaves of C. leprosum were subjected to grinding, extraction in 0.15 M NaCl, protein fractionation (by saturation with ammonium sulfate at 30%, 30 - 60% and 60 - 90%) and exhaustive dialysis of the protein fractions. The samples obtained, crude extract (EB) and protein fractions (F1D, F2D and F3D, obtained from saline saturation and then dialyzed) were evaluated for protein concentration (by the method of Lowry et al., 1951), presence of bioactive lectins (by hemagglutinating activity assays, HA), HA inhibition assays (using carbohydrates) and stability of lectin activity under variable conditions of temperature and pH. Protein fractions were applied to affinity, ion exchange and molecular exclusion chromatographic columns. The collected chromatographic fractions, corresponding to peaks (detected by absorbance reading at 280 nm) were evaluated for protein concentration and HA. The antimicrobial potential of preparations was evaluated on the mycelial growth of Fusarium falciforme and Macrophomina phaseolina as well as on five species of bacteria for the determination of minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). High protein concentration preparations. Elevated lectin activity was also detected in all preparations, with no lectin specificity being revealed to any of the carbohydrates tested. Protein fractions showed lectin activity up to 100 °C (with reduction from 50 °C). The HA varied at different pH values (with reduction in acidic and neutral pH). Chromatographic processes of F1D and F2D in chitin resulted in peaks of material adsorbed and eluted with HA. The preparations did not inhibit the growth of Fusarium falciforme and Macrophomina phaseolina. However, EB, F2D and F3D showed bacteriostatic activity against Staphylococcus aureus
Keywords: Planta; Combretum leprosum; Lectina; Antimicrobiano; Plant; Combretum leprosum; Lectin; Antimicrobial; CIENCIAS BIOLOGICAS::BIOTECNOLOGIA